Pengaruh Paritas, Dukungan Suami, Dan Dukungan Keluarga Terhadap Kepatuhan Pemberian Kolostrum Pada Perawatan Awal Masa Nifas Di RSUD Kabupaten Bekasi - Aristia, Titis; Hasrida (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: to identify one of the supports for the success of breastfeeding is the mother's compliance in providing colostrum in the early days after the birth of the baby. In 2015-2021, 47% of newborns started breastfeeding within an hour of birth, compared to a target of 70%. To determine the influence of parity, husband's support, and family support on compliance with colostrum administration in early postpartum care at the Bekasi Regency Regional Hospital. Methods: This article research is associative analytical research using quantitative methods. Data collection used a cross-sectional approach. The population in this study was all 77 postpartum mothers who had babies aged 0-3 days at the Bekasi District Hospital. The sample for this study was some postpartum mothers who had babies aged 0-3 days, namely 65 postpartum mothers. Data collected using a questionnaire sheet. Data analysis was carried out using the Chi-Square test. Results: parity influences compliance with colostrum administration in early postpartum care, p-value (0.002) < 0.05; husband's support influences compliance with colostrum administration in early postpartum care, p-value (0.000) < 0.05; and family support influences compliance with colostrum administration in early postpartum care, p-value (0.000) < 0.05. Conclusion: the influence of parity, husband's support, and family support on compliance with colostrum feeding in early potential car